Produksi Biodiesel Dari Minyak Nyamplung (Callophyllum Inophyllum) Menggunakan Katalis Lantanum/Lempung : Studi Pemgaruh Suhu Reaksi - Raja Valti Mhd Siregar; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is an alternative energy to replace fossil fuels. It can be synthesized by transesterification process of palm oils. Commonly the process of producing biodiesel was used NaOH or KOH as homogeneous catalyst which has the disadvantage the formation of side products such as soaps and complexity of the separation of catalyst. Several research have developed that using heterogeneous catalys. Synthesis of biodiesel from callophyllum inophyllum oil using metal alloys lanthanum on clay as catalyst. This research studied the effect of temperature reaction with variations 55, 60, 65 oC to the yield of biodiesel produced, and to identifying the characteristics of biodiesel produced. This study begins activation of the catalyst in a way additions H2SO4, impregnation, calcination, oxidation and reduction. Furthermore, to remove impurities and gum contained in the oil was done the degumming process. After that, do the process of transesterification in the three neck flask reactor the mole ratio of methanol : oil 12: 1 and a reaction time 120 minutes. The result, highest biodiesel obtained amounted to 78.41% at the reaction temperature of 60 oC. Physical characterization of biodiesel were done such as density 857 kg/m3, kinematic viscosity 4.735 mm2/s, acid number 0.61 mg-KOH/g biodiesel and flash point 127.5 oC respectively which have accordance with the standards of Indonesian biodiesel (SNI 04-1782-2006).Keywords :La / clay, callophyllum inophyllum oil, degumming, transesterification, biodiesel